(untitled) (Ameghiniana, 2013)
Three new jaw fragments of Xenodontomys simpsoni recovered from Cerro Azul Formation (Huayquerian Land-mammal Age, Late Miocene) of El Guanaco and Barrancas Coloradas (La Pampa) are described. Its dental and mandibular characters confirms both generic and specific status. Xenodontomys is considered more primitive than Palaeoctodon. The diversity displayed by the Huayquerian Ctenomyinae (two genera and probably three species) indicates that the first diversification of this Subfamily is contemporaneous with the first diversification of the typical Octodontinae.